Synergistic effects on process parameters to enhance enzymatic hydrolysis of alkaline oil palm fronds - Md Zain, Masniroszaime; Mohammad, Abdul Wahab; Harun, Shuhaida; Fauzi, Nurul Aina; Hairom, Nur Hanis Hayati (Elsevier, 2018)
Due to an increasing demand for more sustainable and renewable resources, there has been strong interest in utilizing biomass as a source for cleaner production of energy and chemicals. In this work, the lignocellulosic elements of oil palm frond (OPF) biomass were assessed as an alternate sugar feedstock for biofuel and bioproducts production. At present, long hydrolysis times and high enzymatic loadings hinder commercialisation and large-scale utilisation of enzymatic hydrolysis of lignocellulosic biomass. Thus, various process parameters of enzymatic hydrolysis of alkaline OPF fibre were investigated in an attempt to improve process performance. In this study, OPF biomass was pretreated with 4.42% NaOH at 100 °C for 58.31 min, resulting in significant disruption as characterised by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) analysis, and scanning electron microscopy (SEM). Alkaline pretreatment of OPF biomass improved enzymatic biodegradability, and glucan recovery by the Cellic Ctec2 enzyme was more effective than the conventional Celluclast 1.5 L cellulase enzyme. Synergistic effects of stirring speed, surfactant Triton X-100 loading, and β-glucosidase supplement on enzymatic hydrolysis were assessed using statistical experimental design. Under optimal conditions (450 rpm, 1.31%, and 0.14 pNPGU/FPU), 88% conversion of glucan was obtained from alkaline OPF, which is equivalent to the conversion from commercial cellulose (microcrystalline cellulose, MCC). Enzymatic hydrolysis of pretreated OPF was further improved at high agitation speeds. Synergy between agitation speed and surfactant loading interactions with β-glucosidase supplement enhanced glucose production due to the efficient mixing and availability of cellulose to be adsorbed by cellulase.